2020
DOI: 10.1186/s43065-020-00014-x
|View full text |Cite
|
Sign up to set email alerts
|

More than smart pavements: connected infrastructure paves the way for enhanced winter safety and mobility on highways

Abstract: Currently, there is an urgent demand for more cost-effective, resource-efficient and reliable solutions to address safety and mobility challenges on highways enduring snowy winter weather. To address this pressing issue, this commentary proposes that the physical and digital infrastructures should be upgraded to take advantage of emerging technologies and facilitate the vehicle-infrastructure integration (VII), to better inform decision-makers at various levels. Driven by the paradigm shift towards more automa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…2 The University of Hong Kong, Hong Kong, China. 3 CIFI Group, Shanghai, China. 4 The Chinese University of Hong Kong, Hong Kong, China.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The University of Hong Kong, Hong Kong, China. 3 CIFI Group, Shanghai, China. 4 The Chinese University of Hong Kong, Hong Kong, China.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…However, large areas of impervious ground surface could cause many problems, such as the heat island effect, increased surface runoff, and blockage of underground water cycle etc. [1][2][3][4][5]. Pervious concrete, which is designed to be porous to allow permeation of water and air, is being employed to replace the impervious ground pavement so as to combat the above mentioned environmental and drainage problems [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by providing real-time road condition estimations via online platforms (e.g., 511), trip makers will be able to adjust their travel plans and divert accordingly to avoid potential accidents and traffic delays. Likewise, this tool, once refined and tested with more data, can also be integrated into vehicle to everything (V2X) technologies [39][40][41] to provide real-time road surface conditions information for improved safety before, during, and after inclement weather events. Such information can also be utilized by winter road maintenance personnel as the maps would provide information pertaining to dangerous road sections so that maintenance vehicles could be dispatched in a more efficient and timely manner to perform location-specific and targeted maintenance operations to ensure the safety and mobility of the winter travelling public.…”
Section: Three-category Systemmentioning
confidence: 99%
“…Technology-based automation can significantly increase the Pavement Management System's (PMS) efficiency. Some studies have shown the effectiveness of IoT and big data technologies' effectiveness in road and bridge preservation [9].…”
Section: Introductionmentioning
confidence: 99%